2008
DOI: 10.1021/ja805686u
|View full text |Cite
|
Sign up to set email alerts
|

Oxatriquinane and Oxatriquinacene: Extraordinary Oxonium Ions

Abstract: Oxatriquinane, a fused, tricyclic alkyl oxonium ion of unprecented stability, was synthesized in five steps from 1,4,7-cyclononatriene. It survives reflux in H2O, chromatography, and attack by alcohols, alkyl thiols, halide ions, and hindered amine bases. The X-ray crystal structure shows longer C-O bond distances and more acute C-O-C bond angles than any reported alkyloxonium salt. The corresponding oxatriquinene and oxatriquinacene were also synthesized and represent the first examples of stable allyl oxoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 13 publications
2
37
0
1
Order By: Relevance
“…For example, H 4 O 2+ is no longer a minimum energy structure in reaction fields with ε ≥ 3 in a continuum solvent model. 17 Also, examination of the reported, energy minimized structure of Me 3 OH 2+ reveals C–O bond lengths of 1.67 Å. The analogous Et 3 OH 2+ , which has also been implicated in the alkylation of aromatics, 15 has even less plausible C–O bond lengths of 1.74 Å and does not optimize to a minimum energy structure in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…For example, H 4 O 2+ is no longer a minimum energy structure in reaction fields with ε ≥ 3 in a continuum solvent model. 17 Also, examination of the reported, energy minimized structure of Me 3 OH 2+ reveals C–O bond lengths of 1.67 Å. The analogous Et 3 OH 2+ , which has also been implicated in the alkylation of aromatics, 15 has even less plausible C–O bond lengths of 1.74 Å and does not optimize to a minimum energy structure in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…When the mechanical stretching is considered as quite evident and is largely discussed, the chemical stretching has not yet received enough attention. This explains the astonishment shown by the detection of 'abnormally' long bonds, as in the case of single C-C [8] and C-O [9,10] bonds. In fact, the elongated sg eq R of 1.647 Å, 1.659 Å, and 1.704 Å for C-C bond [8] as well as of 1.54 Å [9] and 1.622 Å [10] for C-O bond fall in the first quarter of the bond sg W cov regions as follows from Table 1 and Fig.…”
Section: Quantum-chemical Aspect Of Bond Stretchingmentioning
confidence: 98%
“…Recently, Mascal et al reported the synthesis of oxatriquinane 2 and oxatriquinacene 3, which have a tricyclic condensed ring structure with an oxygen cationic center. 4) Compound 2 was isolated as a crystalline solid suitable for X-ray crystal structure analysis. Interestingly, 2 could be purified by column chromatography and was stable under reflux in alcohol or water.…”
mentioning
confidence: 99%